DNA of the young entrepreneur a way to wealth for young entrepreneurs - McCauley, Sean (HappyAbout.info, 2008)
A compelling mixture of philosophy, personal experience, and practical advice. The book takes the reader on a journey through knowledge, attitudes, values, and actions that spell the difference between success and failure in starting and running a small business, or between running an enterprise on a business-as-usual level and pushing it to great success.